Morphological and molecular characterisation and diagnostics of some species of Scutellonema Andrassy, 1958 (Tylenchida: Hoplolaimidae) with a molecular phylogeny of the genus - Berg, E. van den; Tiedt, L.R.; Coyne, Danny L.; Ploeg, A.T.; Navas-Cortes, J.A.; Roberts, P.A.; Yeates, G.W.; Subbotin, S.A. (Brill, 2013)
Scutellonema spp. are widely distributed across tropical and subtropical regions of the world and are associated with numerous agricultural and horticultural crops. Identification of many Scutellonema species is not always reliable, in part because many species share very similar diagnostic characters. In this study, we provide morphological and molecular characterisation of S.brachyurus from the USA and South Africa, S. bradys from Nigeria and three unidentified species from California, USA, New Zealand and Burkina Faso. Morphological descriptions, measurements, light and scanning electron microscopic photos and drawings are given for S. brachyurus. Females of S. brachyurus from the USA (type A) and South Africa (type B) showed a significant variation in the number of sectors and blocks on the lip annuli, ranging from about 4-12 and from 8-20, respectively. Molecular analysis using the D2-D3 of 28S rRNA, ITS rRNA and the COI mtDNA gene sequences revealed two distinct genotypes within S. brachyurus samples: type A (samples from USA, Italy, Korea, Taiwan) and type B (South Africa). Multivariate analyses determined that S. brachyurus from the USA and Taiwan (type A) differed from that from South Africa (type B) mainly in body, tail and DGO lengths, and ratios b , c , c and V. Phylogenetic relationships within Scutellonema are given as inferred from the analyses of the D2-D3 of 28S rRNA, ITS rRNA and the COI mtDNA gene sequences. PCR-RFLP diagnostic profiles and PCR with species-specific primers are developed for the studied Scutellonema species.